Thermoplastic resin composition and molded article
Patent Information
- Application Number
- JP2024516975
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-14
- Filing Date
- 2023-09-13
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-09-13
AI Technical Summary
【0019】 本発明の熱可塑性樹脂組成物によれば、バイオマス由来のポリアミドを含み、成形性が良好で、耐衝撃性、耐薬品性、長期耐久性に優れるともに、同一又は他の材料からなる部品と動的に接触した際に、軋み音(擦れ音)の発生が抑制される成形品を提供することができる。 本発明の熱可塑性樹脂組成物が、更に、特定のエチレン·α-オレフィン系ゴム質重合体を用いた強化ビニル系グラフト樹脂を含有する場合には、軋み音(擦れ音)の発生が長期的に抑制される成形品を得ることができる。
Smart Images

Figure 0007632746000006 
Figure 0007632746000007 
Figure 0007632746000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition that contains a polyamide made from a raw material derived from biomass (organic resources derived from living organisms such as plants), has good moldability, is excellent in impact resistance, chemical resistance, and long-term durability, and suppresses the generation of creaking noise (rubbing noise) when it comes into dynamic contact with parts made of the same or different materials. The present invention also relates to a molded article of this thermoplastic resin composition. [Background technology]
[0002] Thermoplastic resin compositions are widely used as molding materials for parts of vehicles, office automation (OA) equipment, home appliances, electric and electronic devices, building materials, and the like. Among them, polyamide resins have excellent mechanical strength, chemical resistance, abrasion resistance, and other characteristics, and are therefore used in many applications, including industrial products such as automobiles, electrical, electronic, and mechanical parts, and sports and leisure goods. However, polyamide resins have the disadvantages of poor paintability and impact resistance. In addition, polyamide resins have the problem of being prone to water absorption and large dimensional changes due to their chemical structure. Therefore, much research has been conducted to improve these disadvantages.
[0003] For example, a rubber-modified nylon composition has been proposed in which a carboxylic acid group-containing copolymer obtained by copolymerizing an unsaturated carboxylic acid with styrene or acrylonitrile is used as a compatibilizer, and ABS resin is blended with a polyamide resin (see Patent Document 1).
[0004] It is known that the addition of inorganic fillers such as glass fibers and carbon fibers to polyamide resins dramatically improves the heat resistance, dimensional stability, and rigidity of molded products. For example, a thermoplastic resin composition has been proposed in which glass fibers or carbon fibers are blended into a composition containing polyamide resin and ABS resin (see Patent Document 2). This thermoplastic resin composition is excellent in impact resistance, dimensional stability, rigidity, and heat resistance, and serves as a molding material with a good balance of performance.
[0005] Among the thermoplastic resin parts used in these fields (hereinafter referred to as "parts made of thermoplastic resin composition X"), there are some that are used in combination with other parts, such as thermoplastic resin parts made of the same or different material as thermoplastic resin composition X, cured resin parts, or inorganic material parts made of metal or inorganic compound. For example, the thermoplastic resin parts and other parts are placed in contact with each other, or these parts are placed at a predetermined interval (see Patent Documents 3 and 4). In particular, when thermoplastic resin parts are adjacent to each other (simply in contact with each other, or in contact with each other with a part of an adhesive portion, or in contact with each other with a predetermined interval), it is known that one or both of them move or deform due to vibration, rotation, twisting, sliding, impact, etc., and come into dynamic contact, generating a creaking sound (rubbing sound). It is said that this creaking sound is a sound caused by the stick-slip phenomenon that occurs when two objects rub against each other. The stick-slip phenomenon is said to be a phenomenon different from the conventionally known sliding phenomenon between objects.
[0006] The stick-slip phenomenon is understood as a phenomenon in which frictional force fluctuates greatly periodically, as shown in FIG. 1. Specifically, the stick-slip phenomenon occurs as shown in FIG. 2. That is, when an object M connected with a spring is placed on a drive stage moving at a drive speed V as shown in the model of FIG. 2(a), the object M first moves to the right as shown in FIG. 2(b) together with the stage moving at the drive speed V due to the action of static friction. Then, when the force of the spring trying to return the object to its original position becomes equal to this static frictional force, the object M starts to slip in the direction opposite to the drive speed V. At this time, the object M is subjected to a kinetic frictional force, so the slipping stops at the point in FIG. 2(c) when the force of the spring and this kinetic frictional force become equal. That is, the object M adheres to the drive stage and moves again in the same direction as the drive speed V (FIG. 2(d)). This is called the stick-slip phenomenon. As shown in Figure 1, it is said that when the difference Δμ between the static friction coefficient μs and the friction coefficient μl at the bottom end of the sawtooth waveform is large, creaking noise is more likely to occur. The dynamic friction coefficient is an intermediate value between μs and μl. Therefore, even if the absolute value of the static friction coefficient is small, if Δμ is large, creaking noise is likely to occur. Creaking noise is a major cause of reducing comfort and quietness in car interiors, offices, and residential interiors. For this reason, there is a strong demand for suppressing and reducing the occurrence of creaking noise.
[0007] In recent years, various proposals have been made regarding techniques for suppressing the generation of this creaking noise (rubbing noise). For example, Patent Document 3 discloses a thermoplastic resin composition that contains rubber-reinforced aromatic vinyl resins (A, B), a crystalline thermoplastic resin (C), and a fibrous or layered filler (D), and that has melting points measured in accordance with JIS K7121-1987 in the range of 0 to 100°C and 170 to 280°C and a flexural modulus of elasticity of 3,000 MPa or more.
[0008] Patent Document 4 discloses an automobile interior part made of a thermoplastic resin composition comprising (A) a rubber-reinforced styrene-based resin (A1) obtained by polymerizing a vinyl monomer (b) consisting of an aromatic vinyl compound or an aromatic vinyl compound and another vinyl monomer copolymerizable with the aromatic vinyl compound in the presence of a rubber-based polymer (a) consisting of a conjugated diene-based rubber-based polymer (a-1) and / or an acrylic rubber-based polymer (a-2), and / or 8 to 93 mass % of a styrene-based resin consisting of a styrene-based (co)polymer (A2) of the vinyl-based monomer (b), (B) 5 to 90 mass % of an olefin-based resin, and (C) 2 to 50 mass % of at least one block copolymer selected from block copolymers containing a polymer block mainly consisting of an aromatic vinyl compound and a polymer block mainly consisting of a conjugated diene compound and hydrogenated products thereof, wherein the total of the above components (A), (B) and (C) is 100 mass %.
[0009] When a thermoplastic resin part repeatedly comes into contact with another part, the surface of the thermoplastic resin part may wear away, forming a gap between the thermoplastic resin part and the other part. In order to suppress this, for example, a thermoplastic resin composition containing a polyamide resin as a main component and further containing an inorganic filler is known (see Patent Document 5). However, polyamide resins such as polyamide 6 are prone to moisture absorption and dimensional changes, so it has been difficult to maintain the suppression or reduction of squeak noise over the long term.
[0010] Meanwhile, in recent years, the use of biomass as an alternative to fossil fuel raw materials has been attracting attention in the materials field in order to build a recycling-oriented society. Biomass is an organic compound produced by photosynthesis from carbon dioxide and water. When used, biomass can be converted back into carbon dioxide and water, making it a so-called carbon-neutral raw material (the amount of carbon dioxide emitted and absorbed in the environment is the same, so the increase in carbon dioxide, a greenhouse gas, can be suppressed). Recently, there has been rapid progress in the practical application of biomass plastics made from these biomass raw materials. Attempts are also being made to produce polyamide, a general-purpose polymer material, from these biomass raw materials. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Special Publication No. 7-84549 [Patent Document 2] JP 2002-212383 A [Patent Document 3] International Publication No. 2014 / 175332 [Patent Document 4] JP 2011-168186 A [Patent Document 5] JP 2019-172759 A Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a thermoplastic resin composition containing a biomass-derived polyamide, which has good moldability, excellent impact resistance, chemical resistance, and long-term durability, and which suppresses the generation of creaking noise (rubbing noise) when in dynamic contact with parts made of the same or different materials. [Means for solving the problem]
[0013] The present inventors have found that by blending a biomass-derived polyamide (A) with a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C), and an acid-modified vinyl resin (D) in specific ratios, it is possible to obtain a product with good moldability, excellent impact resistance, chemical resistance, and long-term durability, while also significantly reducing the generation of the above-mentioned creaking noise. The present invention relates to the following.
[0014] [1] A thermoplastic resin composition comprising a polyamide (A) at least a part of which is derived from biomass, a rubber-reinforced vinyl graft resin (B), an aromatic vinyl copolymer resin (C), and an acid-modified vinyl resin (D), A thermoplastic resin composition comprising, per 100 parts by mass in total of polyamide (A), rubber-reinforced vinyl-based graft resin (B), aromatic vinyl-based copolymer resin (C) and acid-modified vinyl-based resin (D), 20 to 70 parts by mass of polyamide (A), 5 to 45 parts by mass of rubber-reinforced vinyl-based graft resin (B), 10 to 75 parts by mass in total of aromatic vinyl-based copolymer resin (C) and acid-modified vinyl-based resin (D), and 0.1 to 40 parts by mass of acid-modified vinyl-based resin (D).
[0015] [2] The rubber-reinforced vinyl-based graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion containing a structural unit derived from a vinyl-based monomer grafted to the rubber polymer (b); 2. The thermoplastic resin composition according to claim 1, wherein the rubbery polymer (b) has a weight average particle size of 0.20 to 0.70 μm.
[0016] [3] The thermoplastic resin composition according to [2], wherein the rubber-reinforced vinyl graft resin (B) contains, as the rubber polymer (b), an ethylene-α-olefin rubber polymer (b1) portion having a melting point of 0 to 100°C as measured in accordance with JIS K7121-1987.
[0017] [4] The thermoplastic resin composition according to [3], wherein the rubber-reinforced vinyl graft resin (B) is obtained by polymerizing a vinyl monomer including an aromatic vinyl compound in the presence of an ethylene-α-olefin rubber polymer (b1) having a melting point of 0 to 100°C as measured in accordance with JIS K7121-1987.
[0018] [5] A molded article made of the thermoplastic resin composition according to any one of [1] to [4]. Effect of the Invention
[0019] According to the thermoplastic resin composition of the present invention, it is possible to provide a molded article which contains a biomass-derived polyamide, has good moldability, and is excellent in impact resistance, chemical resistance, and long-term durability, and which suppresses the generation of creaking noises (rubbing noises) when in dynamic contact with parts made of the same or different materials. When the thermoplastic resin composition of the present invention further contains a reinforced vinyl graft resin using a specific ethylene-α-olefin rubber polymer, it is possible to obtain a molded article in which the generation of creaking noise (rubbing noise) is suppressed for the long term. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is an explanatory diagram of the stick-slip phenomenon. [Diagram 2] Figures 2(a), (b), (c), and (d) are model diagrams of the stick-slip phenomenon. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing an example of a contact state between components. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another example of the contact mode. [Diagram 5]FIG. 5 is a schematic cross-sectional view showing another example of the contact mode. [Figure 6] FIG. 6 is a schematic cross-sectional view showing another example of the contact mode. [Figure 7] FIG. 7 is a schematic cross-sectional view showing another example of the contact mode. [Figure 8] FIG. 8 is a schematic cross-sectional view showing another example of the contact mode. [Figure 9] Figures 9(A), (B) and (C) are schematic diagrams showing other contact modes, where Figure 9(A) is a plan view, Figure 9(B) is a side view and Figure 9(C) is a cross-sectional view taken along line CC in Figure 9(A). [Figure 10] FIG. 10 is a schematic perspective view of the part 20 of FIG. [Figure 11] Figures 11(A), (B) and (C) are schematic diagrams showing other contact modes, where Figure 11(A) is a plan view, Figure 11(B) is a side view and Figure 11(C) is a cross-sectional view taken along line CC in Figure 11(A). [Figure 12] Figures 12(A), (B) and (C) are schematic diagrams showing other contact modes, where Figure 12(A) is a plan view, Figure 12(B) is a side view and Figure 12(C) is a cross-sectional view taken along line CC in Figure 12(A). [Figure 13] FIG. 13 is a schematic perspective view of a part used in another contact mode in FIG. [Figure 14] Figures 14(A), (B) and (C) are schematic diagrams showing other contact modes, where Figure 14(A) is a bottom view, Figure 14(B) is a cross-sectional view taken along line BB in Figure 14(A), and Figure 14(C) is a cross-sectional view taken along line CC in Figure 14(A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, embodiments of the thermoplastic resin composition and the molded article of the present invention will be described in detail.
[0022] As used herein, "(meth)acrylic" means acrylic and / or methacrylic. "(meth)acrylate" means acrylate and / or methacrylate. "(meth)acryloyl" means acryloyl and / or methacryloyl. "(Co)polymer" means a homopolymer and / or a copolymer.
[0023] [Thermoplastic resin composition] The thermoplastic resin composition of the present invention is a thermoplastic resin composition comprising polyamide (A), at least a part of which is derived from biomass, a rubber-reinforced vinyl-based graft resin (B), an aromatic vinyl-based copolymer resin (C), and an acid-modified vinyl-based resin (D), characterized in that, per 100 parts by mass in total of the polyamide (A), the rubber-reinforced vinyl-based graft resin (B), the aromatic vinyl-based copolymer resin (C), and the acid-modified vinyl-based resin (D), the composition contains 20 to 70 parts by mass of polyamide (A), 5 to 45 parts by mass of the rubber-reinforced vinyl-based graft resin (B), 10 to 75 parts by mass in total of the aromatic vinyl-based copolymer resin (C) and the acid-modified vinyl-based resin (D), and 0.1 to 40 parts by mass of the acid-modified vinyl-based resin (D).
[0024] Hereinafter, the biomass-derived polyamide (A) may be simply referred to as "polyamide (A)" or "component (A)". The rubber-reinforced vinyl graft resin (B), aromatic vinyl copolymer resin (C), and acid-modified vinyl resin (D) may be referred to as "component (B)", "component (C)", and "component (D)", respectively.
[0025] Component (B) according to the present invention differs from components (C) and (D) in that component (B) contains a rubber polymer portion, whereas components (C) and (D) do not contain a rubber polymer portion. Components (C) and (D) differ in that component (D) contains acid-modified groups consisting of carboxy groups and / or acid anhydride groups, whereas component (C) does not contain these acid-modified groups.
[0026] As described later, in the production of the rubber-reinforced vinyl-based graft resin (B), a graft copolymer (B-1) is produced in which a resin containing structural units derived from a vinyl-based monomer is chemically bonded to a rubber-based polymer (b), and a resin (B-2) containing structural units derived from a vinyl-based monomer that exists in a free state without being bonded to the rubber-based polymer (b). In the present invention, the graft copolymer (B-1) produced here is defined as the rubber-reinforced vinyl graft resin (B) of component (B), and the resin (B-2) produced at the same time that is not grafted to the rubber polymer is defined as component (C) or component (D). During the production of rubber-reinforced vinyl-based graft resin (B), a very small amount of rubber-like polymer that has no vinyl monomer grafted thereto remains, but since this amount is very small, it is included in the rubber-reinforced vinyl-based graft resin (B).
[0027] Component (B) can be distinguished from components (C) and / or (D) by solvent separation using acetone. The reaction product during the production of rubber-reinforced vinyl graft resin (B) is put into acetone, shaken, and then centrifuged for solid-liquid separation to obtain an acetone-insoluble fraction, which corresponds to component (B). The acetone-soluble fraction corresponds to components (C) and / or (D). The components (C) and (D) according to the present invention may be used in the production of a thermoplastic resin composition as acetone-soluble components produced during the production of component (B), or components (C) and (D) produced separately from the production of component (B) may be used, or both of them may be used.
[0028] <Polyamide (A)> Polyamide (A) is a resin having an acid amide bond (-CO-NH-) in the main chain. Polyamide (A) can be produced by a conventional method, that is, by polymerization of lactam or amino acid having a ring structure, or by condensation polymerization of dicarboxylic acid and diamine. Therefore, homopolyamide, copolyamide, etc. can be used as polyamide (A).
[0029] The polyamide (A) used in the present invention, at least a part of which is derived from biomass, is, for example, polyamide 11, polyamide 610, polyamide 1010, polyamide 410, polyamide MXD10 resin, polyamide 11·6T copolymer resin, etc., and is a polyamide that uses a monomer derived from biomass as at least a part of the raw material. From the viewpoints of easily achieving a carbon neutral effect and of the impact resistance and long-term durability of the molded product, a particularly preferred polyamide (A) is polyamide 11.
[0030] Polyamide 11 is a polyamide having a structure in which monomers having 11 carbon atoms are bonded via amide bonds. Polyamide 11 is usually obtained by using aminoundecanoic acid or undecane lactam as a monomer. In particular, aminoundecanoic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The content of the structural units derived from these monomers having 11 carbon atoms is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of the total structural units of polyamide 11. Polyamide 11 is usually produced by the ring-opening polymerization of the above-mentioned undecane lactam. The polyamide 11 obtained by the ring-opening polymerization is usually subjected to removal of the lactam monomer with hot water, followed by drying and melt extrusion in an extruder.
[0031] Polyamide 610 is a polyamide resin having a structure in which a diamine having 6 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, hexamethylenediamine and sebacic acid are used. Of these, sebacic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The total content of the constitutional units derived from a monomer having 6 carbon atoms and the constitutional units derived from a monomer having 10 carbon atoms is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of all constitutional units of polyamide 610.
[0032] Polyamide 1010 is a polyamide resin having a structure in which a diamine having 10 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, 1,10-decanediamine (decamethylenediamine) and sebacic acid are used. Decamethylenediamine and sebacic acid are monomers obtained from castor oil, and are therefore desirable from the viewpoint of carbon neutrality. The total content of the structural units derived from these monomers having 10 carbon atoms and the structural units derived from monomers having 10 carbon atoms is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of all the structural units of polyamide 1010.
[0033] Polyamide 410 is a polyamide resin having a structure in which a diamine having 4 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, tetramethylenediamine and sebacic acid are used. Sebacic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The total content of the structural units derived from these monomers having 4 carbon atoms and the structural units derived from monomers having 10 carbon atoms is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of all the structural units of polyamide 410.
[0034] The polyamide (A) may be terminated at its ends with a carboxylic acid, an amine, etc. Examples of the carboxylic acid include aliphatic monocarboxylic acids such as caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid. Examples of the amine include aliphatic primary amines such as hexylamine, octylamine, decylamine, laurylamine, myristylamine, palmitylamine, stearylamine, and behenylamine.
[0035] The plant-based content of the polyamide (A) as determined by ASTM6866 (measurement of radioactive carbon 14 C content) is preferably 50% or more, and particularly preferably 80 to 100%.
[0036] The melting point of the polyamide (A) according to JIS K7121-1987 is preferably 160° C. or higher, more preferably 170° C. or higher, from the viewpoint of ease of mixing with the rubber-reinforced vinyl graft resin (B), the aromatic vinyl copolymer resin (C), and the acid-modified vinyl resin (D). There is no particular upper limit to the melting point of the polyamide (A), but it is usually 280° C.
[0037] The thermoplastic resin composition of the present invention may contain only one type of polyamide (A), or may contain two or more types.
[0038] <Rubber-reinforced vinyl graft resin (B)> The rubber-reinforced vinyl graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion containing structural units derived from a vinyl monomer grafted to the rubber polymer (b), and the rubber polymer (b) and the resin (m) portion are chemically bonded to each other. Examples of the rubber polymer (b) in the rubber-reinforced vinyl graft resin (B) include ethylene / α-olefin rubber polymer (b1), diene rubber polymer (b2), acrylic rubber polymer (b3), silicone rubber polymer (b4), etc. From the viewpoints of mechanical properties such as reduced squeak noise and impact resistance, and secondary processability such as plating and paintability, it is preferable to contain ethylene / α-olefin rubber polymer (b1) and / or diene rubber polymer (b2), and it is more preferable to contain ethylene / α-olefin rubber polymer (b1). Therefore, the rubber-reinforced vinyl graft resin (B) is preferably a graft resin obtained by polymerizing a vinyl monomer in the presence of an ethylene-α-olefin rubber polymer and / or a diene rubber polymer (b2), particularly an ethylene-α-olefin rubber polymer (b1).
[0039] (Weight average particle size of rubber polymer (b)) The weight average particle size of the rubber polymer (b) constituting the rubber-reinforced vinyl graft resin (B) is preferably 0.20 to 0.70 μm, more preferably 0.23 to 0.60 μm, and even more preferably 0.25 to 0.50 μm. If the weight average particle size of the rubber polymer (b) is equal to or larger than the lower limit, a thermoplastic resin composition having excellent impact resistance and suppression of creaking noise (rubbing noise) can be obtained. If the weight average particle size of the rubber polymer (b) is equal to or smaller than the upper limit, a thermoplastic resin composition having excellent chemical resistance can be obtained.
[0040] In the present invention, the average particle size of the rubber polymer (b) is a value measured by the following measurement method 1 or measurement method 2.
[0041] <Measuring method 1 for average particle size> The weight average particle size and number average particle size are determined using a Microtrac (manufactured by Nikkiso Co., Ltd., "Nanotrac UPA-EX150" dynamic light scattering method) as a measuring device and pure water as a measuring solvent. This measuring method is mainly used to measure the average particle size of the rubber polymer (b) in the rubber-reinforced vinyl graft resin (B) prepared by emulsion polymerization. Incidentally, it has been confirmed by image analysis using an electron microscope that the average particle size of the rubber polymer (b) dispersed in the latex is equivalent to the average particle size of the rubber polymer (b) in the thermoplastic resin composition.
[0042] <Method 2 for measuring average particle size> In producing the rubber-reinforced vinyl graft resin (B), in the case of solution polymerization in which the rubber polymer (b) is dissolved in a solvent, the particle size of the rubber polymer (b) in the thermoplastic resin composition is measured by image analysis of a transmission electron microscope photograph of the thermoplastic resin composition to determine the weight average particle size (volume average particle size) and number average particle size. This method is primarily used to measure the average particle size of the rubber polymer (b) in the rubber-reinforced vinyl graft resin (B) prepared by solution polymerization.
[0043] (Ethylene-α-olefin rubber polymer (b1)) The ethylene-α-olefin rubber polymer (b1) is a copolymer containing structural units derived from ethylene and structural units derived from an α-olefin. Examples of the α-olefin include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-hexadecene, and 1-eicosene. These α-olefins can be used alone or in combination of two or more. The number of carbon atoms of the α-olefin is preferably 3 to 20, more preferably 3 to 12, and even more preferably 3 to 8, from the viewpoint of the appearance and impact resistance of a molded article obtained by using the thermoplastic resin composition of the present invention.
[0044] The content ratios of the structural units derived from ethylene and the structural units derived from α-olefins constituting the ethylene-α-olefin rubber polymer (b1), when the total of the two is taken as 100 mass%, are preferably 5 to 95 mass% of the structural units derived from ethylene and 5 to 95 mass% of the structural units derived from α-olefins, more preferably 50 to 95 mass% of the structural units derived from ethylene and 5 to 50 mass% of the structural units derived from α-olefins, and even more preferably 60 to 95 mass% of the structural units derived from ethylene and 5 to 40 mass% of the structural units derived from α-olefins, in order to obtain a molded article which has good moldability, excellent impact resistance, chemical resistance and long-term durability, and which suppresses the generation of creaking noises (rubbing noises) when in dynamic contact with parts made of the same or different materials.
[0045] In the present invention, the preferred ethylene-α-olefin rubbery polymer (b1) is an ethylene-α-olefin copolymer having a melting point in the range of 0 to 100°C as measured according to JIS K7121-1987, and may have structural units derived from other monomers. Examples of the other monomers include non-conjugated diene compounds such as alkenylnorbornenes, cyclic dienes, and aliphatic dienes. The structural units derived from other monomers may be used alone or in combination of two or more. The upper limit of the content of the structural units derived from the non-conjugated diene compound is preferably 10% by mass, more preferably 5% by mass, and even more preferably 3% by mass, when the total amount of the structural units constituting the ethylene-α-olefin rubbery polymer (b1) is taken as 100% by mass.
[0046] The melting point of the ethylene-α-olefin rubber polymer (b1) is more preferably 10 to 90°C, and even more preferably 20 to 80°C, in order to obtain a molded product which has good moldability, impact resistance, chemical resistance, and which suppresses the generation of creaking noise (rubbing noise) when dynamically contacted with parts made of the same or different materials. The melting point of the ethylene-α-olefin rubber polymer (b1) being in the range of 0 to 100°C means that this rubber polymer has crystallinity. If the ethylene-α-olefin rubber polymer (b1) has a crystalline portion, it is considered that the occurrence of the stick-slip phenomenon is suppressed, and the occurrence of squeaking noise due to contact with parts made of the same or different materials is reduced.
[0047] The ethylene-α-olefin rubbery polymer (b1) is preferably an ethylene-α-olefin copolymer comprising structural units derived from ethylene and structural units derived from an α-olefin, since the effects of the present invention can be fully obtained. As the ethylene-α-olefin rubbery polymer (b1), in particular, an ethylene-propylene copolymer, an ethylene-1-butene copolymer, or an ethylene-1-octene copolymer is preferred, with an ethylene-propylene copolymer being particularly preferred. These ethylene-α-olefin rubbery polymers (b1) can be used alone or in combination of two or more kinds.
[0048] (Diene rubber polymer (b2)) Examples of the diene rubber polymer (b2) include homopolymers such as polybutadiene and polyisoprene; butadiene copolymers such as styrene-butadiene copolymer, styrene-butadiene-styrene copolymer, acrylonitrile-styrene-butadiene copolymer, and acrylonitrile-butadiene copolymer; isoprene copolymers such as styrene-isoprene copolymer, styrene-isoprene-styrene copolymer, and acrylonitrile-styrene-isoprene copolymer. These may be random copolymers or block copolymers. The diene rubbery polymer (b2) may be either a crosslinked polymer or a non-crosslinked polymer. These diene rubbery polymers (b2) can be used alone or in combination of two or more kinds.
[0049] (Acrylic rubber polymer (b3)) The acrylic rubber polymer (b3) is not particularly limited, but is preferably a (co)polymer of a (meth)acrylic acid alkyl ester compound having an alkyl group with 1 to 8 carbon atoms, or a copolymer of this (meth)acrylic acid alkyl ester compound and a vinyl monomer copolymerizable therewith.
[0050] Specific examples of the acrylic acid alkyl ester compound used here in which the alkyl group has 1 to 8 carbon atoms include methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, i-butyl acrylate, amyl acrylate, hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, etc. Specific examples of methacrylic acid alkyl ester compounds include methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, amyl methacrylate, hexyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, and cyclohexyl methacrylate. Of these compounds, n-butyl acrylate and 2-ethylhexyl acrylate are preferred, and n-butyl acrylate is particularly preferred. These can be used alone or in combination of two or more.
[0051] These acrylic rubber polymers (b3) can be used alone or in combination of two or more kinds.
[0052] (Silicone rubber polymer (b4)) The silicone rubber polymer (b4) is not particularly limited, but is preferably a polyorganosiloxane having a vinyl polymerizable functional group, and from the viewpoint of color development, a silicone / acrylic composite rubber is preferred. The silicone / acrylic composite rubber is preferably a silicone / acrylic composite rubber in which polyorganosiloxane and alkyl (meth)acrylate polymer are combined. The silicone / acrylic composite rubber can be produced, for example, according to the method described in JP 2016-125006 A.
[0053] These silicone rubber polymers (b4) can be used alone or in combination of two or more kinds.
[0054] The vinyl monomer forming the resin (m) portion of the rubber-reinforced vinyl graft resin (B) is not particularly limited, but may mainly be an aromatic vinyl compound, a vinyl cyanide compound, a (meth)acrylic acid ester compound, a maleimide compound, a vinyl monomer that gives a structural unit having a carboxy group, as described below, a vinyl monomer that gives an acid anhydride group, a vinyl monomer that has other functional groups, etc. Among these, it is preferable to use an aromatic vinyl compound and a vinyl cyanide compound.
[0055] The aromatic vinyl compound is not particularly limited as long as it has at least one vinyl bond and at least one aromatic ring.Examples of aromatic vinyl compounds include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, β-methylstyrene, ethylstyrene, p-tert-butylstyrene, vinyltoluene, vinylxylene, vinylnaphthalene, etc. Among these, styrene and α-methylstyrene are preferred, and styrene is particularly preferred.These compounds can be used alone or in combination of two or more.
[0056] Examples of the vinyl cyanide compound include acrylonitrile, methacrylonitrile, ethacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, etc. Among these, acrylonitrile is preferred. These can be used alone or in combination of two or more.
[0057] Examples of the (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0058] Examples of the maleimide-based compound include maleimide, N-methylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-dodecylmaleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-benzylmaleimide, N-naphthylmaleimide, N-cyclohexylmaleimide, etc. These may be used alone or in combination of two or more. In order to introduce a structural unit derived from a maleimide-based compound into a polymer chain, for example, a method can be applied in which an unsaturated dicarboxylic acid anhydride is copolymerized with maleic anhydride, followed by imidization.
[0059] Examples of vinyl monomers (carboxyl-containing unsaturated compounds) that provide structural units having a carboxyl group include (meth)acrylic acid, ethacrylic acid, maleic acid, fumaric acid, itaconic acid, crotonic acid, and cinnamic acid. Among these, methacrylic acid is preferred. These can be used alone or in combination of two or more.
[0060] Examples of vinyl monomers (unsaturated acid anhydrides) that provide structural units having an acid anhydride group include maleic anhydride, itaconic anhydride, citraconic anhydride, etc. These can be used alone or in combination of two or more.
[0061] In addition to the above vinyl monomers, vinyl monomers having at least one functional group selected from a hydroxy group, an amino group, an epoxy group, and an oxazoline group can also be used.
[0062] For example, examples of vinyl monomers having a hydroxy group (hydroxy group-containing unsaturated compounds) include (meth)acrylic acid esters having a hydroxy group, such as hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate; o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, o-hydroxy-α-methylstyrene, m-hydroxy-α-methylstyrene, p- Examples of the hydroxymethyl-α-methylstyrene include hydroxymethyl-α-methylstyrene, 2-hydroxymethyl-α-methylstyrene, 3-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-α-methylstyrene, 4-hydroxymethyl-1-vinylnaphthalene, 7-hydroxymethyl-1-vinylnaphthalene, 8-hydroxymethyl-1-vinylnaphthalene, 4-hydroxymethyl-1-isopropenylnaphthalene, 7-hydroxymethyl-1-isopropenylnaphthalene, 8-hydroxymethyl-1-isopropenylnaphthalene, p-vinylbenzyl alcohol, 3-hydroxy-1-propene, 4-hydroxy-1-butene, cis-4-hydroxy-2-butene, trans-4-hydroxy-2-butene, and 3-hydroxy-2-methyl-1-propene. These can be used alone or in combination of two or more.
[0063] Examples of vinyl monomers having an amino group (amino group-containing unsaturated compounds) include aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminomethyl acrylate, diethylaminomethyl acrylate, 2-dimethylaminoethyl acrylate, aminoethyl methacrylate, propylaminoethyl methacrylate, dimethylaminomethyl methacrylate, diethylaminomethyl methacrylate, 2-dimethylaminoethyl methacrylate, phenylaminoethyl methacrylate, p-aminostyrene, N-vinyldiethylamine, N-acetylvinylamine, acrylamine, methacrylamine, N-methylacrylamine, etc. These can be used alone or in combination of two or more.
[0064] Examples of vinyl monomers (epoxy group-containing unsaturated compounds) that provide structural units having an epoxy group include glycidyl (meth)acrylate, 3,4-oxycyclohexyl (meth)acrylate, vinyl glycidyl ether, allyl glycidyl ether, methallyl glycidyl ether, etc. These may be used alone or in combination of two or more.
[0065] Examples of vinyl monomers having an oxazoline group (unsaturated compounds containing an oxazoline group) include vinyl oxazoline, 4-methyl-2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 2-vinyl-4,4-dimethyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, 2-isopropenyl-4,4-dimethyl-2-oxazoline, etc. These may be used alone or in combination of two or more.
[0066] The resin (m) portion is preferably a resin (m1) portion containing a structural unit derived from an aromatic vinyl compound and a structural unit derived from a vinyl cyanide compound, and a resin (m2) portion containing a structural unit derived from an aromatic vinyl compound, a structural unit derived from a vinyl cyanide compound, and a structural unit derived from a vinyl monomer that provides a structural unit having a carboxy group, i.e., a structural unit derived from a carboxy group-containing unsaturated compound and / or an unsaturated acid anhydride, and more preferably a resin (m1) portion containing a structural unit derived from an aromatic vinyl compound and a structural unit derived from a vinyl cyanide compound.
[0067] When the resin (m) portion is a resin (m1) portion containing structural units derived from an aromatic vinyl compound and structural units derived from a vinyl cyanide compound, the lower limit of the proportion of the total amount of structural units derived from an aromatic vinyl compound and structural units derived from a vinyl cyanide compound in a total of 100% by mass of structural units derived from vinyl monomers forming the resin (m) portion is preferably 50% by mass, more preferably 70% by mass, and even more preferably 90% by mass, from the viewpoint of the appearance and impact resistance of a molded article obtained using the thermoplastic resin composition of the present invention.
[0068] From the viewpoint of the appearance, impact resistance and color tone of a molded article obtained using the thermoplastic resin composition of the present invention, the content ratio of the structural units derived from aromatic vinyl compounds and the structural units derived from vinyl cyanide compounds contained in the resin (m1) part is preferably 50 to 95 mass% of structural units derived from aromatic vinyl compounds and 5 to 50 mass% of structural units derived from vinyl cyanide compounds, more preferably 60 to 85 mass% of structural units derived from aromatic vinyl compounds and 15 to 40 mass% of structural units derived from vinyl cyanide compounds, and even more preferably 65 to 80 mass% of structural units derived from aromatic vinyl compounds and 20 to 35 mass% of structural units derived from vinyl cyanide compounds.
[0069] When the resin (m) portion is a resin (m2) portion further containing a structural unit derived from a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride, the content of the structural unit derived from the carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride is preferably 0.1 to 20 mass%, more preferably 1 to 20 mass%, and even more preferably 2 to 8 mass% in the total 100 mass% of the structural units derived from the vinyl monomers forming the resin (m2). If it is within the above range, a molded product having good moldability, impact resistance, chemical resistance, long-term durability, and molded appearance can be obtained. The content ratio of the structural units derived from an aromatic vinyl compound and the structural units derived from a vinyl cyanide compound in the resin (m2) part is preferably the same as that in the resin (m1) part.
[0070] The content ratio of the rubber polymer (b) part and the resin (m) part contained in the rubber-reinforced vinyl graft resin (B) is preferably 20 to 90 mass% of the rubber polymer (b) part and 10 to 80 mass% of the resin (m) part, more preferably 25 to 84 mass% of the rubber polymer (b) part and 16 to 75 mass% of the resin (m) part, and even more preferably 30 to 77 mass% of the rubber polymer (b) part and 23 to 70 mass% of the resin (m) part, when the total of both is taken as 100 mass%, since a molded article having good moldability, excellent impact resistance, chemical resistance, and long-term durability and suppressing the generation of creaking noise (rubbing noise) when dynamically contacting parts made of the same or other materials can be obtained.
[0071] The graft ratio of the rubber-reinforced vinyl graft resin (B) of component (B) is usually 10 to 150%, preferably 15 to 120%, more preferably 20 to 100%, and particularly preferably 30 to 80%. When the graft ratio of component (B) is within the above range, the impact resistance and moldability of the resulting thermoplastic resin composition become even better.
[0072] The graft ratio of the component (B) can be calculated by the following formula (1). Graft ratio (mass%)=((ST) / T)×100 … (1) In the above formula (1), S is the mass (g) of the insoluble matter obtained by adding 1 g of component (B) or a mixture of component (B) and component (C) and / or component (D) obtained by the above production method by graft polymerization to 20 mL of acetone, shaking for 2 hours using a shaker at 25°C, and then centrifuging for 60 minutes using a centrifuge (rotation speed: 23,000 rpm) at 5°C to separate the insoluble matter from the soluble matter. T is the mass (g) of the rubber polymer (b) contained in 1 g of component (B). The mass of the rubber polymer (b) can be obtained by a method of calculation from the polymerization recipe and the polymerization conversion rate, or by a method of determination by infrared absorption spectroscopy (IR), pyrolysis gas chromatography, CHN elemental analysis, or the like.
[0073] The graft ratio of component (B) can be adjusted by appropriately selecting, for example, the type and amount of chain transfer agent used in the graft polymerization when producing component (B), the type and amount of polymerization initiator used, the method and addition time of the monomer components during polymerization, the polymerization temperature, etc.
[0074] The thermoplastic resin composition of the present invention may contain only one type of rubber-reinforced vinyl graft resin (B), or may contain two or more types of rubber-reinforced vinyl graft resin (B) that differ in the type, composition, physical properties, etc. of structural units.
[0075] As described above, the rubber polymer (b) of the rubber-reinforced vinyl-based graft resin (B) may be an ethylene-α-olefin-based rubber polymer (b1), a diene-based rubber polymer (b2), an acrylic-based rubber polymer (b3), a silicone-based rubber polymer (b4), etc. Therefore, the rubber-reinforced vinyl-based graft resin (B) may be a graft resin containing an ethylene-α-olefin-based rubber polymer (b1) as the rubber polymer (b), a graft resin containing a diene-based rubber polymer (b2) as the rubber polymer (b), a graft resin containing an acrylic-based rubber polymer (b3) as the rubber polymer (b), a graft resin containing a silicone-based rubber polymer (b4) as the rubber polymer (b), etc., and two or more of these may be used in combination. From the viewpoint of reducing squeak noise, it is preferable to use a rubber-reinforced vinyl graft resin (B) containing an ethylene-α-olefin rubber polymer (b1) as the rubber polymer (b) alone. In order to impart impact resistance, plating property, paintability, etc., it is preferable to use a rubber-reinforced vinyl graft resin (B) containing an ethylene-α-olefin rubber polymer (b1) as the rubber polymer (b) in combination with a rubber-reinforced vinyl graft resin (B) containing a diene rubber polymer (b2) as the rubber polymer (b).
[0076] The rubber-reinforced vinyl graft resin (B) can be produced, for example, by graft polymerizing a vinyl monomer consisting of an aromatic vinyl compound and, if desired, another vinyl compound copolymerizable with the aromatic vinyl compound in the presence of a rubber polymer (b) such as an ethylene-α-olefin rubber polymer (b1) having a melting point (Tm) of 0 to 100°C. The polymerization method in this production method is not particularly limited as long as the component (B) which is a graft copolymer can be obtained, and a known method can be applied. As the polymerization method, emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, or a combination of these polymerization methods can be used. In these polymerization methods, known polymerization initiators, chain transfer agents (molecular weight regulators), emulsifiers, etc. can be appropriately used.
[0077] In the above-mentioned production method, a mixed product is usually obtained from the above-mentioned component (B), which is a graft copolymer (B-1) in which a (co)polymer of vinyl monomers is graft-polymerized to a rubber polymer (b), and the above-mentioned component (C) and / or component (D), which is a (co)polymer resin (B-2) in which vinyl monomers are not graft-polymerized to the rubber polymer (b). In some cases, the mixed product may also contain a rubber polymer (b) to which the (co)polymer is not graft-polymerized. The thermoplastic resin composition of the present invention contains the components (B), (C), and (D) as essential components. In other words, the thermoplastic resin composition of the present invention contains both the above-mentioned component (B) and the components (C) and (D) as essential components. Therefore, the mixed product of the above-mentioned component (B) and the components (C) and / or (D) produced as described above can be used as the raw material of the thermoplastic resin composition of the present invention as the components (B), (C), and / or (D).
[0078] The graft copolymer (B-1) which is the component (B) can be separated from the mixed product of the component (B) and the resin (B-2) which is the component (C) and / or the component (D) by solvent separation using acetone. Specifically, the mixed product of the component (B) and the component (C) and / or the component (D) is put into acetone, shaken, and then centrifuged, whereby the component (B) is obtained as an acetone insoluble matter, and the component (C) and / or the component (D) is obtained as an acetone soluble matter. Therefore, the raw material of component (B) in the thermoplastic resin composition of the present invention may be an acetone-insoluble fraction separated by the acetone separation from a mixed product of the component (B) and the component (C) and / or the component (D). Similarly, the raw material of component (C) and / or the component (D) in the thermoplastic resin composition of the present invention may be an acetone-soluble fraction separated by the acetone separation from a mixed product of the component (B) and the component (C) and / or the component (D). The components (B), (C) and (D) may be mixtures produced by mixing the separated components (B) and (C) and / or (D).
[0079] <Aromatic vinyl copolymer resin (C)> The aromatic vinyl copolymer resin (C) is a copolymer having structural units derived from vinyl monomers including at least an aromatic vinyl compound. The aromatic vinyl copolymer resin (C) preferably has the same structural unit composition as the resin (m1) portion described above, including structural units derived from an aromatic vinyl compound and structural units derived from a vinyl cyanide compound.
[0080] The aromatic vinyl copolymer resin (C) may be one produced as resin (B-2) during the production of component (B), or may be one obtained by copolymerizing a vinyl monomer containing an aromatic vinyl compound separately from this resin (B-2) without using a rubber polymer, or may contain both. When component (C) produced as resin (B-2) during the production of component (B) and component (C) produced separately without using a rubber-like polymer are used, the vinyl monomer compositions and physical properties of the components may be different or the same.
[0081] The intrinsic viscosity (in methyl ethyl ketone, 30°C) of component (C) in the thermoplastic resin composition of the present invention is usually 0.1 to 1.5 dL / g, preferably 0.15 to 1.2 dL / g, and more preferably 0.15 to 1.0 dL / g. When the intrinsic viscosity is within the above range, the impact resistance and moldability of the thermoplastic resin composition of the present invention are improved.
[0082] The intrinsic viscosity [η] of component (C) and component (D) described below was measured by the following method. First, the acetone-soluble portion of component (C) or component (D), or the mixed product of component (B) and component (C) and / or component (D), is dissolved in methyl ethyl ketone to prepare five different concentrations. Using an Ubbelohde viscometer, the reduced viscosity of each concentration is measured at 30°C, and the intrinsic viscosity [η] (dL / g) is calculated from the results.
[0083] The thermoplastic resin composition of the present invention may contain only one type of component (C), or may contain two or more types that differ in the type, composition, physical properties, etc. of structural units.
[0084] <Acid-modified vinyl resin (D)> The acid-modified vinyl resin (D) is a copolymer having at least an acid-modified group, i.e., a structural unit derived from a vinyl monomer having a carboxyl group and / or an acid anhydride group. The acid-modified vinyl resin (D) preferably has a structural unit composition similar to that of the resin (m2) described above, including a structural unit derived from an aromatic vinyl compound, a structural unit derived from a vinyl cyanide compound, and a structural unit derived from a carboxyl group-containing unsaturated compound and / or an unsaturated acid anhydride.
[0085] The acid-modified vinyl resin (D) may be one produced as resin (B-2) during the production of component (B), or may be one obtained by copolymerizing a vinyl monomer containing an aromatic vinyl compound and a vinyl cyanide compound, and a carboxyl-containing unsaturated compound and / or an unsaturated acid anhydride, without using a rubber-like polymer, separately from this resin (B-2), or may contain both. When component (D) produced as resin (B-2) during the production of component (B) and component (D) produced separately without using a rubber polymer are used, the vinyl monomer compositions and physical properties of the components may be different or the same.
[0086] The intrinsic viscosity (in methyl ethyl ketone, 30°C) of component (D) in the thermoplastic resin composition of the present invention is usually 0.1 to 1.5 dL / g, preferably 0.15 to 1.2 dL / g, and more preferably 0.15 to 1.0 dL / g. When the intrinsic viscosity is within the above range, the impact resistance and moldability of the thermoplastic resin composition of the present invention are improved.
[0087] The thermoplastic resin composition of the present invention may contain only one type of component (D), or may contain two or more types that differ in the type, composition, physical properties, etc. of structural units.
[0088] <Content of each ingredient> The content of component (A) in the thermoplastic resin composition of the present invention is 20 to 70 parts by mass, preferably 25 to 65 parts by mass, and more preferably 30 to 60 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D). If the content of component (A) is equal to or higher than the lower limit, the impact resistance, chemical resistance, and squeak noise reduction effect due to the inclusion of component (A) are excellent. In addition, the carbon neutral effect can be improved by including biomass-derived polyamide (A). If the content of component (A) is equal to or lower than the upper limit, the contents of other components (B) to (D) can be secured, resulting in excellent long-term durability.
[0089] The content of component (B) in the thermoplastic resin composition of the present invention is 5 to 45 parts by mass, preferably 7 to 40 parts by mass, and more preferably 10 to 35 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D). If the content of component (B) is equal to or higher than the lower limit, the impact resistance and squeak noise reduction effect due to the inclusion of component (B) are excellent. If the content of component (B) is equal to or lower than the upper limit, the contents of other components (A), (C), and (D) can be secured, resulting in excellent chemical resistance.
[0090] In the case where two or more kinds of components (B) are used in combination, for example, when a rubber-reinforced vinyl graft resin (B) containing an ethylene-α-olefin rubber polymer (b1) as the rubber polymer (b) and a rubber-reinforced vinyl graft resin (B) containing a diene rubber polymer (b2) as the rubber polymer (b) are used in combination, the respective contents in the thermoplastic resin composition of the present invention are, from the viewpoint of reducing squeak noise, 5 to 30 parts by mass of the rubber-reinforced vinyl graft resin (B) containing the ethylene-α-olefin rubber polymer (b1), 5 to 30 parts by mass of the diene rubber polymer (b2) per 100 parts by mass of the total of the components (A), (B), (C) and (D). The amount of the rubber-reinforced vinyl graft resin (B) containing the ethylene-α-olefin rubber polymer (b1) is preferably 30 to 1 part by mass, more preferably 10 to 30 parts by mass of the rubber-reinforced vinyl graft resin (B) containing the ethylene-α-olefin rubber polymer (b1) and 20 to 1 part by mass of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2), and even more preferably 10 to 30 parts by mass of the rubber-reinforced vinyl graft resin (B) containing the ethylene-α-olefin rubber polymer (b1) and 10 to 1 part by mass of the rubber-reinforced vinyl graft resin (B) containing the diene rubber polymer (b2).
[0091] As described above, the weight average particle size of the rubber polymer (b) of the component (B) used in the present invention is preferably 0.20 to 0.70 μm, particularly 0.23 to 0.60 μm, and especially 0.25 to 0.50 μm. Component (B) may contain a rubber-reinforced vinyl-based graft resin (B) containing a rubber-like polymer (b) outside the above range of weight-average particle size. However, if the rubber-reinforced vinyl-based graft resin (B) containing a rubber-like polymer (b) having a weight-average particle size of less than 0.15 μm is contained, the impact resistance and the effect of suppressing the generation of creaking noise (rubbing noise) of the obtained thermoplastic resin composition tend to be inferior. For this reason, when the thermoplastic resin composition of the present invention contains a rubber-reinforced vinyl graft resin (B) containing a rubber polymer (b) having a weight average particle size of less than 0.15 μm, the content thereof is preferably 45 parts by mass or less, particularly 30 parts by mass or less, and especially 0 to 20 parts by mass, per 100 parts by mass of the total of components (A), (B), (C) and (D). In the present invention, of the total mass 100% of component (B), it is preferable that 30% by mass or more, particularly 50% by mass or more, and especially 70 to 100% by mass is rubber-reinforced vinyl graft resin (B) containing a rubber polymer (b) having a weight average particle size of 0.20 to 0.70 μm.
[0092] The total content of components (C) and (D) contained in the thermoplastic resin composition of the present invention is 20 to 65 parts by mass, preferably 25 to 60 parts by mass, and more preferably 30 to 55 parts by mass, per 100 parts by mass of the total of components (A), (B), (C), and (D). If the total content of components (C) and (D) is equal to or greater than the lower limit, the impact resistance and long-term durability of the component (C) and component (D) are excellent. If the total content of components (C) and (D) is equal to or less than the upper limit, the content of other components (A) and (B) can be ensured, resulting in excellent impact resistance and chemical resistance.
[0093] The content of component (D) in the thermoplastic resin composition of the present invention is 0.1 to 40 parts by mass, preferably 2 to 38 parts by mass, and more preferably 5 to 36 parts by mass, per 100 parts by mass of the total of components (A), (B), (C) and (D). Component (D) is effective in suppressing hydrolysis of component (A) and improving the compatibility of component (A) with components (B) and (C). If the content of component (D) is equal to or higher than the lower limit, a thermoplastic resin composition having excellent effects of component (D) and excellent impact resistance, long-term durability, and suppression of squeak noise can be obtained. If the content of component (D) is too high, the components (D) react with each other, deteriorating the moldability and molded appearance of the thermoplastic resin composition. For this reason, the content of component (D) is set to equal to or lower than the upper limit.
[0094] From the viewpoint of impact resistance and long-term durability, it is preferable that the content of only component (C) be less than 45 parts by mass, particularly less than 40 parts by mass, and even more particularly less than 35 parts by mass, per 100 parts by mass of the total of components (A) and (B) (C) and (D).
[0095] In the production of component (B), the resin (B-2) produced together with the above-mentioned graft copolymer (B-1) may not be able to be determined as component (C) or component (D) depending on the type of vinyl monomer used in the production of component (B). In general, when the vinyl monomer used in the production of component (B) contains the above-mentioned carboxy-containing unsaturated compound and / or unsaturated acid anhydride, the resin (B-2) can be regarded as component (D). When it does not contain the carboxy-containing unsaturated compound and / or unsaturated acid anhydride, the resin (B-2) is regarded as component (C).
[0096] The content of the rubber polymer (b) derived from component (B) and contained in the thermoplastic resin composition of the present invention is preferably 5 to 80 parts by mass, more preferably 10 to 70 parts by mass, further preferably 15 to 65 parts by mass, and particularly preferably 20 to 60 parts by mass, per 100 parts by mass of the total of components (B), (C), and (D). When the content of the rubber polymer (b) is within the above range, the mechanical strength and the effect of reducing squeak noise of the molded article made of the thermoplastic resin composition of the present invention are further improved.
[0097] For the same reasons as for the content of the rubber-reinforced vinyl graft resin (B) containing the rubber-like polymer (b) having a weight-average particle diameter of 0.20 to 0.07 μm in the above-mentioned rubber-reinforced vinyl graft resin (B), it is preferable that 30 mass % or more, particularly 50 mass % or more, and especially 70 to 100 mass % of the total amount of the rubber-like polymer (b) contained in the thermoplastic resin composition of the present invention is a rubber-like polymer (b) having a weight-average particle diameter of 0.20 to 0.70 μm. For the same reasons as in the case of the rubber-reinforced vinyl graft resin (B) containing the rubber polymer (b) having a weight-average particle diameter of less than 0.15 μm, the rubber polymer (b) having a weight-average particle diameter of less than 0.15 μm is preferably 70 mass% or less, particularly 50 mass% or less, and even more preferably 0 to 30 mass%, of the total amount of the rubber polymer (b) contained in the thermoplastic resin composition of the present invention (100 mass%).
[0098] <Melt Volume Rate (MVR)> The melt volume rate (MVR) of the thermoplastic resin composition of the present invention is 10 to 70 cm under the conditions of 240°C and 98N. 3 / 10min, especially 15~60cm 3 / 10min, especially 20~50cm 3 When the MVR is equal to or higher than the above lower limit, the moldability is excellent. When the MVR is equal to or lower than the above upper limit, the mechanical strength such as impact resistance is excellent. The MVR of the thermoplastic resin composition of the present invention is measured by the method described in the Examples section below.
[0099] <Plant level> From the viewpoint of carbon neutrality, the plant-based content of the thermoplastic resin composition of the present invention is preferably 20% or more, more preferably 25% or more, and even more preferably 30% or more. There is no particular upper limit to the plant-based content of the thermoplastic resin composition of the present invention, but from the viewpoint of blending the necessary amounts of components (B), (C) and (D) with respect to the biomass-derived polyamide (A), it is usually 70% or less. Here, the plant-based content of the thermoplastic resin composition of the present invention is determined as a percentage obtained by multiplying the mass proportion of the biomass-derived polyamide (A) in the thermoplastic resin composition by the plant-based content of the biomass-derived polyamide (A).
[0100] <Abnormal noise risk index> In a test performed using a ZIEGLER stick-slip tester "SSP-02" according to the method described in the Examples below, the thermoplastic resin composition of the present invention preferably has an abnormal noise risk index of 5 or less, more preferably 3 or less, measured under conditions of a temperature of 23°C, a humidity of 50% RH, a load of 5N, and a speed of 1 mm / sec. According to the standard (VDA203-260) of the German Association of the Automotive Industry, an abnormal noise risk index of 3 or less is acceptable. Such a preferable abnormal noise risk index can be satisfied by appropriately adjusting the blending amounts of the components (A) to (D), etc.
[0101] <Method of producing thermoplastic resin composition> The thermoplastic resin composition of the present invention can be obtained by mixing component (A), component (B), component (C), and component (D) and other components as desired in a desired blending ratio and melt-kneading. As described above, when component (B) is produced by graft polymerization, component (C) and / or component (D) are also produced, so a mixture of component (B) and component (C) and / or component (D) is obtained. The mixture of component (B) and component (C) and / or component (D) can be used as a raw material as it is. In addition, component (C) and / or component (D) produced separately from component (B) can be additionally mixed into the mixture. Component (C) and / or component (D) produced during the production of component (B) may have the same or different physical properties such as copolymerization composition and intrinsic viscosity as component (C) and / or component (D) produced separately from the production of component (B).
[0102] Examples of components other than the components (A) to (D) that can be blended into the thermoplastic resin composition of the present invention include nucleating agents, lubricants, heat stabilizers, antioxidants, UV absorbers, antiaging agents, plasticizers, antibacterial agents, colorants, fillers, etc. These components can be blended within a range that does not impair the object of the present invention.
[0103] The filler to be used is preferably in the form of fibers or layers. Examples of fibrous fillers include inorganic fibers such as glass fibers and ceramic whiskers, and organic fibers such as carbon fibers and aramid fibers. Examples of layer-like fillers include scaly or flat fillers, such as montmorillonite, hectorite, vermiculite, saponite, and glass flakes.
[0104] When the thermoplastic resin composition of the present invention contains a filler, the content of the filler is preferably 5 to 50 parts by mass, more preferably 8 to 35 parts by mass, and particularly preferably 10 to 25 parts by mass, relative to 100 parts by mass in total of components (A), (B), (C), and (D). When the content of the filler is within the above range, the rigidity of the obtained molded article is more excellent, which is preferable.
[0105] The thermoplastic resin composition of the present invention may contain other thermoplastic resins other than the components (A) to (D) as necessary, within the scope of the present invention. Examples of other thermoplastic resins include polyvinyl chloride, polymethyl methacrylate resin, polycarbonate (PC) resin, polylactic acid resin, polystyrene resin, high-impact polystyrene resin, ASA resin, etc. Polyamide resins not derived from biomass may be blended. These may be used alone or in combination of two or more.
[0106] When a thermoplastic resin other than the components (A) to (D) is blended into the thermoplastic resin composition of the present invention, from the viewpoint of effectively obtaining the effects of the present invention by using the components (A) to (D) in a predetermined ratio, the content of the thermoplastic resin other than the components (A) to (D) is preferably 50 parts by mass or less per 100 parts by mass of the total of the components (A) to (D) and the other thermoplastic resin.
[0107] The thermoplastic resin composition of the present invention can be produced by mixing the components in a predetermined mixing ratio using a tumbler mixer, a Henschel mixer, or the like, and then melt-kneading the components under appropriate conditions using a kneading machine such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader, a roll, a feeder ruder, etc. A preferred kneading machine is a twin-screw extruder. When the components are kneaded, they may be kneaded together or may be divided and kneaded in multiple stages. After kneading with a Banbury mixer or kneader, the components may be pelletized with an extruder. Among the fillers, fibrous ones are preferably fed from the middle of the extruder by a side feeder in order to prevent them from being cut during kneading. The melt-kneading temperature is usually 200 to 300°C, and preferably 220 to 280°C.
[0108] [Molded products] The molded article obtained by molding the thermoplastic resin composition of the present invention can be used as at least one component of an article that includes at least two components that come into contact with each other, thereby preventing the article from generating creaking noise.
[0109] According to the present invention, there is provided an article including at least two parts in contact with each other, at least one of which is a molded article made of the thermoplastic resin composition of the present invention (hereinafter, this may be referred to as the "article of the present invention"). In this case, it is preferable that two or more parts are molded articles made of the thermoplastic resin composition of the present invention, and it is particularly preferable that all of the parts are molded articles made of the thermoplastic resin composition of the present invention.
[0110] There is no limitation on the method for producing the above molded article or part from the thermoplastic resin composition of the present invention. For example, injection molding, injection compression molding, gas-assisted molding, press molding, blow molding, and profile extrusion molding can be mentioned. In addition, known methods such as film and sheet molding, such as calendar molding and T-die extrusion molding, can be mentioned.
[0111] The thermoplastic resin composition of the present invention is suitable as a molding material for an article in which at least two of the parts of the article are in constant or intermittent contact with each other, and the contacting parts move or collide slightly with each other when an external force such as vibration, twisting, impact, etc. is applied to the article. The contacting manner of the contacting parts may be any of surface contact, line contact, point contact, etc., and may be partially bonded.
[0112] Specifically, examples of such an article include an article in which one surface of part 10 and one surface of part 20 are butted together and bonded together as shown in FIG. 3; and an article in which a portion of part 10 is in contact with and fitted into a recess formed in part 20 as shown in FIGS. 4 to 8.
[0113] Specific examples of articles in which parts are in contact with each other in a fitted state include the following (1) to (4). (1) An article in which one end of part 10 is in contact with a complementary recess formed in part 20 in a snug fit, as shown in FIG. (2) As shown in FIG. 5, each end of part 10 is in contact with a complementary recess formed in a corner of part 20 in a snug fit state. (3) As shown in FIG. 6, an article in which each end of a part 20 is in contact with a complementary recess formed in each of two parts 10 arranged approximately parallel to each other in a closely fitted state. (4) As shown in FIG. 7, part 20 having an outer surface dimension that is the same as the inner surface dimension of part 10 is inserted into part 10 in a nested manner, and the inner and outer surfaces of both parts are in contact with each other in a tightly fitted state.
[0114] The two parts in the article of the present invention do not need to fit together perfectly, but may fit together with a certain amount of gap or play as shown in Fig. 8, and may be such that they repeatedly come into and out of contact with each other when an external force such as vibration, twisting, or impact is applied to the article.
[0115] Examples of articles having a combination of contact portions as described above include articles as shown in Figures 9(A) to (C). In the articles in Figures 9(A) to (C), part 10 is a box-shaped part consisting of a rectangular parallelepiped with the entire bottom surface open. Part 20 is a molded product that has the same shape as part 10 and has a rectangular opening formed in the center of the top surface. As shown in Figures 9(A) to (C), part 20 can be fitted into part 10. The outer peripheral surface of part 20 and the inner peripheral surface of part 10 are in contact with each other, and when they are subjected to an external force such as vibration, they slightly deform and repeatedly come into and out of contact. As shown in Fig. 10, part 20 has protrusions 30 on opposing outer surfaces. As shown in Fig. 9(A) to (C), part 10 has holes on two opposing side surfaces for accommodating protrusions 30 of part 20. When part 10 is fitted into part 20, protrusions 30 snap-fit into the holes, preventing the two parts from easily coming loose.
[0116] By molding at least one of the parts 10 and 20 with the thermoplastic resin composition of the present invention, it is possible to prevent the generation of creaking noise, for example, even when an external force is applied in the direction of the arrow in Fig. 9(C). The direction of the external force is not limited to the direction in Fig. 9(C), and even when an external force is applied from another direction, the generation of creaking noise is prevented when at least one of the parts 10 and 20 is molded with the thermoplastic resin composition of the present invention. The cross-sectional shape of the protrusion 30 and the shape of the hole in the part 10 in Figs. 9(A) to (C) can be changed to change the configuration so that both parts are press-fitted.
[0117] 11(A)-(C) show the same embodiment as the article of FIG. 9(A)-(C), except that instead of the projection 30 and the hole that snap-fits thereto, the parts 10 and 20 are bonded to parts of the inner and outer surfaces of the parts 10 and 20 using adhesive 31. Instead of the adhesive 31, the parts 10 and 20 can be welded to each other by laser welding or the like. This method is convenient when both parts are thermoplastic resin molded products. In particular, in laser welding, it is preferable to combine a part made of a transparent thermoplastic resin that transmits laser light with a part made of a thermoplastic resin that absorbs laser light. Specific products include instruments such as an in-vehicle speedometer, lighting, etc.
[0118] 12(A)-(C) show an embodiment similar to that of the article of FIG. 9(A)-(C), except that holes are provided at opposing positions on opposing side surfaces of part 10 and part 20, and the two parts are fixed together by fastening with bolts and nuts 33 through these two holes. Instead of bolts and nuts, parts 10 and 20 may be fixed together using screws, pins, rivets, bushings, brackets, hinges, nails, etc.
[0119] As shown in Fig. 13, an article such as that shown in Fig. 14(A) to (C) including a part 18 having a rectangular plate-like main body and cylindrical shafts 19 protruding outward in the longitudinal direction from both ends, and a frame-like part 28 into which the shaft 19 of part 18 is inserted and which supports part 18 rotatably around the shaft 19, is also suitable for molding with the thermoplastic resin composition of the present invention. By molding at least one of part 18 and part 28 with the thermoplastic resin composition of the present invention, it is possible to suppress the generation of creaking noise when part 18 is rotated around shaft 19 or when an external force such as vibration is applied to the article.
[0120] 14(A) to 14(C), when a frame-like part 28 has a plurality of openings 29, the article can be suitably used as a device that adjusts the amount and direction of air flow by adjusting the angle of the part 18. Examples of such devices include air outlets of home and car air conditioners, air purifiers, fans, etc.
[0121] In the above-mentioned article, the generation of squeak noise can be significantly reduced by forming at least one of the parts 10, 18 and the parts 20, 28 from the thermoplastic resin composition of the present invention. The other article may also be formed from the thermoplastic resin composition of the present invention.
[0122] Materials constituting parts made of materials other than the thermoplastic resin composition of the present invention include various thermoplastic resins, thermosetting resins, rubber, organic materials, inorganic materials, and metal materials.
[0123] Examples of thermoplastic resins constituting parts made of materials other than the thermoplastic resin composition of the present invention include polyvinyl chloride, polyethylene, polypropylene, AS resin, ABS resin, AES resin, ASA resin, polymethyl methacrylate resin, polystyrene resin, impact-resistant polystyrene resin, ethylene-vinyl acetate (EVA) resin, polyamide (PA) resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polycarbonate (PC) resin, polylactic acid resin, PC / ABS resin, PC / AES resin, PA / ABS resin, PA / AES resin, etc. These can be used alone or in combination of two or more.
[0124] Examples of thermosetting resins constituting parts made of materials other than the thermoplastic resin composition of the present invention include phenolic resins, epoxy resins, urea resins, melamine resins, unsaturated polyester resins, etc. These can be used alone or in combination of two or more.
[0125] Examples of rubber constituting parts made of materials other than the thermoplastic resin composition of the present invention include chloroprene rubber, polybutadiene rubber, ethylene-propylene rubber, various synthetic rubbers such as SEBS, SBS, and SIS, natural rubber, etc. These may be used alone or in combination of two or more kinds.
[0126] Examples of organic materials constituting parts made of materials other than the thermoplastic resin composition of the present invention include insulation board, MDF (medium density fiberboard), hardboard, particleboard, lumber core, LVL (laminated veneer lumber), OSB (oriented structural board), PSL (parallel board), WB (wafer board), hard fiberboard, soft fiberboard, lumber core plywood, board core plywood, special core plywood, veneer core plywood, laminated sheets and boards of paper impregnated with tap resin, boards made by mixing adhesive with fine pieces and linear bodies of crushed (used) paper, etc. and compressing them under heat, various wood materials, etc. These can be used alone or in combination of two or more kinds.
[0127] Examples of inorganic materials constituting parts made of materials other than the thermoplastic resin composition of the present invention include calcium silicate board, flexible board, homocement board, gypsum board, sheathing gypsum board, reinforced gypsum board, gypsum lath board, decorative gypsum board, composite gypsum board, various ceramics, glass, etc. These can be used alone or in combination of two or more.
[0128] Examples of metal materials constituting parts made of materials other than the thermoplastic resin composition of the present invention include iron, aluminum, copper, various alloys, etc. These can be used alone or in combination of two or more.
[0129] Of these, thermoplastic resins, thermosetting resins, and rubbers are preferred, and ABS resins, AES resins, PC resins, ABS resins, PC / AES resins, and polymethyl methacrylate resins are particularly preferred.
[0130] When at least one of the parts of the article of the present invention is molded from the thermoplastic resin composition of the present invention, the generation of creaking noise is suppressed even if the parts are repeatedly brought into and out of contact with each other due to vibration, sliding, etc. Therefore, the article of the present invention can be suitably used as an automobile part, an office machine part, a housing part, a home appliance part, etc.
[0131] When an automobile part is molded from the thermoplastic resin composition of the present invention, it is possible to significantly reduce the generation of creaking noise, for example, even when the part repeatedly comes into and out of contact with other parts due to vibrations while the vehicle is running. When the thermoplastic resin composition of the present invention contains a diene rubber, it has excellent fracture properties at low temperatures and is therefore particularly suitable for use in automobile interior parts. Examples of such automobile parts include door trims, door linings, pillar garnishes, consoles, door pockets, ventilators, ducts, air conditioner blades, valve shutters, louvers, meter visors, instrument panel upper garnishes, instrument panel lower garnishes, A / T indicators, on-off switches (slide parts, slide plates), grill front defrosters, grill side defrosters, lid clusters, cover installers, masks (mask switches, mask radios, etc.), glove boxes, pockets (pocket decks, pocket cards, etc.), steering wheel horn pads, switch parts, exterior parts for car navigation systems, etc. Among these, the material can be particularly suitably used as ventilators, air conditioner blades, valve shutters, louvers, switch parts, exterior parts for car navigation systems, etc.
[0132] When an office equipment part is molded from the thermoplastic resin composition of the present invention, it is possible to significantly reduce the generation of creaking noise even when the part repeatedly comes into contact with and out of contact with other parts due to, for example, vibration during operation of the equipment or opening and closing of a desk drawer.
[0133] When a housing component is molded from the thermoplastic resin composition of the present invention, it is possible to significantly reduce the generation of creaking noise, even when the component repeatedly comes into contact with and out of contact with other components, for example, when a door or sliding door is opened and closed.
[0134] When a home appliance part is molded from the thermoplastic resin composition of the present invention, it is possible to significantly reduce the generation of creaking noise, for example, even when the part repeatedly comes into contact with and disengages from other parts due to vibration during operation of the appliance. Examples of such home appliance parts include exterior parts such as cases and housings, interior parts, parts around switches, parts of moving parts, etc.
[0135] The molded article of the present invention not only reduces the generation of creaking noise, but also has a good feel and high rigidity, and is therefore particularly suitable for use as, for example, parts of electric or electronic devices, optical devices, lighting devices, office equipment, or home appliances, automotive interior parts, residential interior parts, etc. Among these, it is particularly suitable for parts of vehicles such as automobiles that may be touched by the hands, for example, grips such as assist grips, as well as parts such as handles and doorknobs, and portable items.
[0136] Examples of parts of electric or electronic devices and optical devices include housings and covers of cameras such as digital video cameras and still cameras, which are often touched by hand; housings and covers of handheld computers, mobile phones, personal digital assistants, and the like.
[0137] Lighting equipment parts include ceiling light panels, covers, connectors, and switch parts.
[0138] Examples of parts for office equipment include exterior parts such as cases and housings, interior parts, parts around switches, movable parts, desk lock parts, desk drawers, and paper trays for copiers.
[0139] Examples of parts for home appliances include exterior parts such as cases and housings, interior parts, parts around switches, and moving parts.
[0140] Examples of automobile interior parts include grips such as doorknobs, handles, and assist grips, as well as door trims, door linings, pillar garnishes, consoles, console boxes, center panels, door pockets, ventilators, ducts, air conditioners, meter visors, instrument panel upper garnishes, instrument panel lower garnishes, A / T indicators, on-off switches (slide portions, slide plates), switch bezels, grill front defrosters, grill side defrosters, lid clusters, cover installers, masks (mask switches, mask radios, etc.), glove boxes, pockets (pocket decks, pocket cards, etc.), steering wheel horn pads, switch parts, and exterior parts for car navigation systems.
[0141] Examples of interior parts for housing include doorknobs, shelf doors, chair dampers, movable parts for folding table legs, door opening and closing dampers, sliding door rails, curtain rails, etc. EXAMPLES
[0142] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following, parts and percentages are by weight unless otherwise specified.
[0143] [Measurement and evaluation method] The methods for measuring and evaluating various physical properties and characteristics in the following examples and comparative examples are as follows.
[0144] (1) Measurement of Melt Volume Rate (MVR) The thermoplastic resin composition was measured according to the ISO 1133 standard. The MVR is an index of the flowability, i.e., moldability, of a thermoplastic resin composition.
[0145] (2) Evaluation of resistance to moist heat aging by melt volume rate (MVR) Pellets of the thermoplastic resin composition were left to stand in a thermo-hygrostat "PL-2SPH" manufactured by Espec Corp. under conditions of 60°C and 80% RH for 500 hours, and then the pellets were taken out of the thermo-hygrostat and the melt volume rate (MVR) was measured as described above. The rate of change in MVR was calculated using the following formula. The smaller the rate of change, the better the moist heat aging properties. Change in MVR due to moist heat aging (%) = (MVR after moist heat aging / MVR before moist heat aging) x 100
[0146] (3) Impact resistance evaluation based on V-notch Charpy impact strength The thermoplastic resin composition was injection molded using a Toshiba Machine injection molding machine "IS-170FA" (product name) at a cylinder temperature of 250°C, injection pressure of 80 MPa, and mold temperature of 60°C, and a molded piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm was taken. The V-notched Charpy impact strength (kJ / m 2 ) was measured.
[0147] (4) Evaluation of moisture absorption impact resistance by V-notch Charpy impact strength The above V-notched molded specimen for the Charpy test was left to stand in an Espec Corporation thermo-hygrostat PL-2SPH for 168 hours at 23°C and 50% RH, after which the specimen was removed from the thermo-hygrostat and the above-mentioned Charpy impact strength was measured, and the rate of change in Charpy impact strength was calculated using the following formula. The closer the rate of change is to 100%, the less moisture absorption it exhibits. Change in Charpy impact strength due to moisture absorption (%) = (Charpy impact strength after moisture absorption / Charpy impact strength before moisture absorption) x 100
[0148] (5) Evaluation of chemical resistance using sunscreen cream A rectangular test piece (150 mm x 10 mm x 2 mm) made by injection molding of a thermoplastic resin composition under the same conditions as in (3) above was fixed along a bending form method test jig having a surface with a gradually changing curvature. Next, a chemical solution was applied to the test piece and left in an environment of 23°C for 48 hours. After leaving it, the test piece was checked for the occurrence of crazes and cracks, and the limit strain [%] was calculated from the curvature of the test jig. A sunscreen cream (Shiseido's "Anessa") was used as the chemical solution. The higher the critical strain value, the better the chemical resistance.
[0149] (6) Measurement of creaking noise evaluation (abnormal noise risk index) after thermal degradation The thermoplastic resin composition was injection molded using a Toshiba Machine injection molding machine "IS-170FA" (product name) under the conditions of a cylinder temperature of 250°C, an injection pressure of 50MPa, and a mold temperature of 60°C. A molded product of length 150 mm, width 100 mm, and thickness 4 mm was obtained, and test pieces of length 60 mm, width 100 mm, thickness 4 mm and length 50 mm, width 25 mm, and thickness 4 mm were cut out with a disk saw. Next, the ends of the test pieces were chamfered with sandpaper of grit #100, and then fine burrs were removed with a cutter knife to obtain two test pieces for evaluating creaking noise, one large and one small. The above evaluation test pieces were left in an oven adjusted to 80°C ± 5°C for 300 hours, and then cooled at 25°C for 24 hours to obtain heat-aged evaluation test pieces. The two heat-aged test pieces, one large and one small, were set in a ZIEGLER stick-slip tester "SSP-02" and rubbed together three times with an amplitude of 20 mm under conditions of a temperature of 23°C, humidity of 50% RH, load of 5 N, and speed of 1 mm / sec, to measure the abnormal noise risk index. The higher the abnormal noise risk index, the more likely it is that squeak noise will occur. This test method is performed by thermal aging, so it is also possible to evaluate the sustainability of the squeak noise reduction effect.
[0150] (7) Evaluation of creaking noise after moisture absorption (abnormal noise risk index) The above-mentioned creaking noise evaluation test specimen was left in an oven adjusted to 80°C ± 5°C for 300 hours, and then cooled at 25°C for 24 hours to thermally age the evaluation specimen, which was then left to stand for 168 hours in an Espec Corporation constant temperature and humidity chamber "PL-2SPH" at 25°C and 50% RH. The abnormal noise risk index of the obtained evaluation specimen was measured in the same manner as above.
[0151] (8) Heat resistance (HDT) The deflection temperature was measured using a 1.8 MPa load, flatwise method, in accordance with ISO 75-2:2013 edition.
[0152] [Raw materials used] In the following Examples and Comparative Examples, the raw materials used in the production of the thermoplastic resin compositions are the following commercially available products or those produced according to the following Production Examples.
[0153] <Polyamide (A)> As the polyamide (A), the following commercially available product was used. PA11: Arkema's "Rilsan BMNO" (Polyamide 11, vegetable content: 100%, melting point: 190°C) PA1010: Daicel-Evonik's "Vestamid Terra DS22" (Polyamide 1010, vegetable content: 100%, melting point: 200°C) PA610: Arkema's "Rilsan SMVO" (Polyamide 610, vegetable content: 62%, melting point: 225°C)
[0154] <Production Example 1: Production of a mixed product of component (B1) and component (C1)> A 20-liter stainless steel autoclave equipped with a ribbon-type agitator blade, a continuous auxiliary addition device, a thermometer, etc. was charged with 30 parts of ethylene-propylene copolymer (ethylene / propylene = 78 / 22 (%), Mooney viscosity (ML1 + 4, 100 ° C) 20, melting point (Tm): 40 ° C, glass transition temperature (Tg): -50 ° C) as an ethylene-α-olefin rubber polymer, 50 parts of styrene, 20 parts of acrylonitrile, 0.5 parts of t-dodecyl mercaptan, and 110 parts of toluene, and the internal temperature was raised to 75 ° C. The contents of the autoclave were stirred for 1 hour to obtain a homogeneous solution. Then, 0.45 parts of t-butylperoxyisopropyl monocarbonate was added, and the internal temperature was further raised. After reaching 100 ° C., the polymerization reaction was carried out with the stirring speed at 100 rpm while maintaining this temperature. After 4 hours from the start of the polymerization reaction, the internal temperature was raised to 120° C., and the reaction was continued for an additional 2 hours while maintaining this temperature, and the polymerization reaction was completed. The polymerization conversion rate was 98%.
[0155] Thereafter, the internal temperature was cooled to 100°C, and 0.2 parts of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenol)-propionate and 0.02 parts of dimethyl silicone oil; KF-96-100cSt (product name: manufactured by Shin-Etsu Silicones Co., Ltd.) were added, after which the reaction mixture was extracted from the autoclave, and unreacted materials and the solvent were removed by steam distillation. The volatile matter was then substantially degassed using a 40mmφ vented extruder (cylinder temperature 220°C, vacuum degree 760mmHg) and pelletized.
[0156] In the obtained ethylene-α-olefin rubber-reinforced aromatic vinyl resin (B1) (a mixture of rubber-reinforced vinyl graft resin (B), component (B1), and aromatic vinyl copolymer resin (C), component (C1)), the content of ethylene-α-olefin rubber polymer was 30% (calculated from the polymerization conversion), the acetone insoluble matter was 47%, the acetone soluble matter was 53%, the graft ratio was 55%, the intrinsic viscosity [η] of the acetone soluble matter was 0.33 dL / g, and the melting point measured according to JIS K7121-1987 was 40°C. The weight average particle diameter (volume average particle diameter) and number average particle diameter of the ethylene-α-olefin rubber polymer in the solution polymerization system, which were determined by the above-mentioned measurement method 2 (resolution processing of transmission electron microscope photographs), were 0.45 μm and 0.35 μm, respectively.
[0157] <Production Example 2: Production of a mixed product of component (B2) and component (C2)> 100 parts of the same ethylene-propylene copolymer as used in Production Example 1, 20 parts of maleic anhydride-modified polyethylene (Mitsui Chemicals, Inc., "Mitsui Hiwax 2203A", mass average molecular weight: 2,700, acid value: 30 mg / g) as an acid-modified olefin polymer, and 5 parts of potassium tallow fatty acid (a mixture of potassium oleate, potassium stearate, and potassium palmitate) as an anionic emulsifier were mixed. This mixture was fed from the hopper of a twin-screw extruder (Ikegai Corporation, "PCM30", L / D=40) at 4 kg / Hr, and was melt-kneaded and extruded while continuously feeding an aqueous solution of 0.5 parts of potassium hydroxide and 2.4 parts of ion-exchanged water from a feed port provided at the vent of the twin-screw extruder. The molten mixture was continuously fed to a cooling device attached to the tip of the twin-screw extruder and cooled to 90°C. The solid discharged from the tip of the twin-screw extruder was then poured into 80°C warm water and continuously dispersed, diluting the solid concentration to about 40% to obtain an aqueous dispersion of olefin resin. The particle size of the ethylene-α-olefin rubber polymer in the obtained olefin resin was measured by the above-mentioned measurement method 1 (dynamic light scattering method), and the weight average particle size was 0.40 μm (number average particle size: 0.26 μm).
[0158] An olefin resin aqueous dispersion (60 parts as solid content of ethylene-propylene copolymer) was placed in a stainless steel polymerization tank equipped with a stirrer, ion-exchanged water was added to the olefin resin aqueous dispersion so that the solid content concentration became 30%, 0.006 parts of ferrous sulfate, 0.3 parts of sodium pyrophosphate, 0.35 parts of fructose, and 1.0 parts of tallow fatty acid potassium (mixture of potassium oleate, potassium stearate, and potassium palmitate) were charged, and the temperature was raised to 80°C. 30 parts of styrene, 10 parts of acrylonitrile, and 1.0 parts of cumene hydroperoxide were continuously added to the mixture for 150 minutes, and emulsion polymerization was carried out while maintaining the polymerization temperature at 80°C, to obtain an aqueous dispersion containing an ethylene-α-olefin rubber-reinforced aromatic vinyl resin. An antioxidant was added to the aqueous dispersion containing the rubber-modified graft polymer, and the solid content was precipitated with sulfuric acid. After the processes of dehydration, washing, and drying, a powdered ethylene-α-olefin rubber-reinforced aromatic vinyl resin was obtained.
[0159] In the obtained ethylene / α-olefin rubber-reinforced aromatic vinyl resin (B2) (a mixture of rubber-reinforced vinyl graft resin (B), component (B2), and aromatic vinyl copolymer resin (C), component (C2)), the ethylene / α-olefin rubber polymer content was 60% (calculated from the polymerization conversion rate), the acetone insoluble matter was 84%, the acetone soluble matter was 16%, the graft ratio was 40%, the intrinsic viscosity [η] of the acetone soluble matter was 0.37 dL / g, and the melting point measured in accordance with JIS K7121-1987 was 42°C.
[0160] The average particle size measurements for the following components (B3) and (B5) were performed using the above-mentioned Measurement Method 1 (dynamic light scattering method).
[0161] <Production Example 3: Production of a mixed product of component (B3) and component (C3)> In a 7-liter glass flask equipped with a stirrer, 75 parts of ion-exchanged water, 0.5 parts of potassium rosinate, 0.1 parts of t-dodecyl mercaptan, 40 parts (solids) of polybutadiene rubber latex (weight average particle size: 0.40 μm, number average particle size: 0.26 μm, gel content: 85%), 15 parts of styrene, and 5 parts of acrylonitrile were added in a nitrogen stream, and the mixture was heated with stirring. When the internal temperature reached 45° C., a solution of 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate heptahydrate, and 0.2 parts of glucose dissolved in 20 parts of ion-exchanged water was added, and the mixture was further stirred. Then, 0.07 parts of cumene hydroperoxide was added to initiate polymerization. After polymerization for 1 hour, 50 parts of ion-exchanged water, 0.7 parts of potassium rosinate, 45 parts of styrene, 15 parts of acrylonitrile, 0.05 parts of t-dodecyl mercaptan, and 0.01 parts of cumene hydroperoxide were continuously added over 3 hours. Polymerization was continued for 1 hour, and 0.2 parts of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) were added to complete the reaction. The polymerization conversion rate was 98%. The resin component was coagulated from the latex, which was the reaction product, with an aqueous sulfuric acid solution, washed with water, and then dried to obtain a rubber-reinforced aromatic vinyl resin (B3) (a mixture of component (B3) which is a rubber-reinforced vinyl graft resin (B) and component (C3) which is an aromatic vinyl copolymer resin (C)).
[0162] In the obtained butadiene rubber reinforced aromatic vinyl resin, the polybutadiene rubber content was 40% (measured by pyrolysis gas chromatography), the acetone insoluble matter was 67%, the acetone soluble matter was 33%, the graft ratio was 68%, the intrinsic viscosity [η] of the acetone soluble matter was 0.45 dL / g, and no melting point was observed as measured in accordance with JIS K7121-1987.
[0163] <Production Example 4: Production of a mixed product of component (B4) and component (D4)> The synthesis was carried out in the same manner as in Production Example 3, except that the styrene and acrylotryl were changed to 43 parts of styrene, 14 parts of acrylotryl, and 3 parts of methacrylic acid. The obtained butadiene rubber-reinforced aromatic vinyl resin (B4) (a mixture of component (B4) which is a rubber-reinforced vinyl graft resin (B) and component (D4) which is an acid-modified vinyl resin (D). This mixture may also contain aromatic vinyl copolymer resin (C), but only in a very small amount. It is referred to as a mixture of component (B4) and component (D4)) had a polybutadiene rubber content of 40% (measured using pyrolysis gas chromatography), an acetone insoluble content of 52%, an acetone soluble content of 48%, a graft ratio of 30%, an intrinsic viscosity [η] of the acetone soluble content of 0.56 dL / g, and no melting point was observed as measured according to JIS K7121-1987.
[0164] <Production Example 5: Production of a mixed product of component (B5) and component (C5)> In a 7-liter glass flask equipped with a stirrer, 75 parts of ion-exchanged water, 0.5 parts of potassium rosinate, 0.1 parts of t-dodecyl mercaptan, 40 parts (solids) of polybutadiene rubber latex (weight average particle size: 0.10 μm, number average particle size: 0.08 μm, gel content: 85%), 15 parts of styrene, and 5 parts of acrylonitrile were added in a nitrogen stream, and the mixture was heated with stirring. When the internal temperature reached 45° C., a solution of 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate heptahydrate, and 0.2 parts of glucose dissolved in 20 parts of ion-exchanged water was added, and the mixture was further stirred. Then, 0.07 parts of cumene hydroperoxide was added to initiate polymerization. After polymerization for 1 hour, 50 parts of ion-exchanged water, 0.7 parts of potassium rosinate, 45 parts of styrene, 15 parts of acrylonitrile, 0.05 parts of t-dodecyl mercaptan, and 0.01 parts of cumene hydroperoxide were continuously added over 3 hours. Polymerization was continued for 1 hour, and 0.2 parts of 2,2'-methylene-bis(4-ethyl-6-t-butylphenol) were added to complete the reaction. The polymerization conversion rate was 98%. The resin component of the latex, which was the reaction product, was coagulated with an aqueous sulfuric acid solution, washed with water, and then dried to obtain a rubber-reinforced aromatic vinyl resin (B5) (a mixture of component (B5) which is a rubber-reinforced vinyl graft resin (B) and component (C5) which is an aromatic vinyl copolymer resin (C)).
[0165] In the obtained butadiene rubber reinforced aromatic vinyl resin, the polybutadiene rubber content was 40% (measured by pyrolysis gas chromatography), the acetone insoluble matter was 67%, the acetone soluble matter was 33%, the graft ratio was 68%, the intrinsic viscosity [η] of the acetone soluble matter was 0.45 dL / g, and no melting point was observed as measured in accordance with JIS K7121-1987.
[0166] <Aromatic vinyl resin (C)> The AS resin "SAN-H" (product name) (intrinsic viscosity [η]: 0.80 dL / g) manufactured by Techno UMG was used.
[0167] <Production Example 6: Production of Acid-Modified Vinyl Resin (D)> In a reactor equipped with a stirrer, 250 parts of water, 3 parts of sodium laurate, 0.2 parts of t-dodecyl mercaptan, 0.4 parts of sodium formaldehyde sulfoxylate, 0.0025 parts of ferrous sulfate, 0.01 parts of disodium ethylenediaminetetraacetate, and 0.5 parts of cumene hydroperoxide were charged, and the inside of the reactor was deoxygenated. Then, 73 parts of α-methylstyrene were charged while stirring at 60°C in a nitrogen stream. After sufficient emulsification, 17 parts of acrylonitrile, which is a component other than α-methylstyrene, were continuously dropped over 5 hours to carry out copolymerization, and the polymerization was terminated when the polymerization conversion rate reached 85.0%. Next, 0.5 parts of cumene hydroperoxide, 0.05 parts of t-dodecyl mercaptan, 0.4 parts of sodium formaldehyde sulfoxylate, 0.0025 parts of ferrous sulfate, and 0.01 parts of disodium ethylenediaminetetraacetate were further charged into the polymerization solution. Then, 2 parts of styrene, 3 parts of acrylonitrile, and 5 parts of methacrylic acid were continuously dropped over 0.5 hours while stirring at 60°C in a nitrogen stream to carry out copolymerization. After the dropwise addition, the mixture was stirred at 60°C for 1.5 hours to terminate the polymerization. The final polymerization conversion rate was 96.0%. The amount of residual monomers in the reactor was 1.4% α-methylstyrene, 0.2% styrene, 1.2% acrylonitrile, and 1.2% methacrylic acid relative to the total amount of monomers used in polymerization. Thereafter, the mixture was solidified with calcium chloride, and an acid-modified vinyl resin (D) having an intrinsic viscosity [η] of 0.31 dL / g was recovered using a vented extruder "DMG40mm" (model name) manufactured by Nippon Placon Co., Ltd.
[0168] <Filling material> Glass fiber: Owens Corning glass fiber "MA FT698" (product name) (fibrous, fiber length 3 mm, fiber diameter 13 μm) was used.
[0169] <Other thermoplastic resins> PA6: A polyamide resin "Novamid 1015" (product name) manufactured by Mitsubishi Engineering Plastics Corporation (polyamide 6, vegetable-based content: 0%, melting point: 225°C) was used.
[0170] [Examples 1 to 30, Comparative Examples 1 to 9] The components shown in Tables 1 to 5 were mixed in the blending ratios shown in Tables 1 to 5 using a Henschel mixer, and then the mixture was melt-kneaded using a twin-screw extruder (manufactured by Japan Steel Works, Ltd., TEX44α, barrel set temperature 250°C) and pelletized to obtain a thermoplastic resin composition. The thermoplastic resin composition thus obtained was subjected to the above-mentioned measurements and evaluations, and the results are shown in Tables 1 to 5. In addition, Tables 1 to 5 also show the plant-based content of the produced thermoplastic resin compositions.
[0171] [Table 1]
[0172] [Table 2]
[0173] [Table 3]
[0174] [Table 4]
[0175] [Table 5]
[0176] The following can be seen from Tables 1 to 5. Examples 1 to 30 were within the range of the requirements of the present invention, and therefore had good moldability, impact resistance, chemical resistance, long-term durability, and excellent squeak noise suppression. On the other hand, Comparative Examples 1 and 2, which did not contain polyamide (A), were inferior in long-term durability and squeak noise suppression. Comparative Examples 3 and 4, in which the blending amount of polyamide (A) was outside the range of the present invention, were inferior in any one of impact resistance, chemical resistance, and long-term durability. Comparative Examples 5 and 6, in which the amount of rubber-reinforced vinyl resin (B) was outside the range of the present invention, were inferior in any one of impact resistance, chemical resistance, and squeak noise suppression. Comparative Examples 7 and 8 were inferior in any one of moldability, impact resistance, and squeak noise suppression because the blending amount of the acid-modified vinyl resin (D) was outside the range of the present invention. Comparing Example 26 with Comparative Example 9, it can be seen that even when a filler such as glass fiber is added, by blending polyamide (A), it is possible to achieve excellent impact resistance and long-term durability. Examples 27 to 30 are examples using a rubber-reinforced aromatic vinyl resin (B5) containing a rubber-like polymer (b) having a weight average particle diameter of 0.10 μm as the rubber-reinforced vinyl graft resin (B), but the Charpy impact strength and the abnormal sound risk index are inferior to other examples not using the rubber-reinforced aromatic vinyl resin (B5) containing such a small particle diameter rubber-like polymer (b). This tendency is also evident in Example 27, which uses a very small amount of rubber-reinforced aromatic vinyl resin (B5).
[0177] Although the present invention has been described in detail using specific embodiments, it will be apparent to those skilled in the art that various modifications are possible within the scope of the invention. This application is based on Japanese patent application No. 2022-165619 filed on October 14, 2022, the entirety of which is incorporated by reference. [Industrial Applicability]
[0178] The thermoplastic resin composition of the present invention has excellent moldability and can be suitably used as a molding material for molded articles that require impact resistance, chemical resistance, long-term durability, and suppression of creaking noise. [Explanation of symbols]
[0179] 10, 18, 20, 28 parts 19 Axis 29 Opening 30 protrusions 31 Adhesive 33 Bolts and nuts
Claims
1. A thermoplastic resin composition comprising: a polyamide (A) obtained by using a monomer obtained from castor oil, at least a part of which is derived from biomass; a rubber-reinforced vinyl-based graft resin (B) which is a graft copolymer (B-1) in which a resin containing a structural unit derived from a vinyl-based monomer is chemically bonded; an aromatic vinyl-based copolymer resin (C) (containing a resin (B-2) which is not grafted to a rubber polymer); and an acid-modified vinyl-based resin (D) (containing a resin (B-2) which is not grafted to a rubber polymer), The composition contains 20 to 67 parts by mass of polyamide (A), 5 to 32 parts by mass of rubber-reinforced vinyl-based graft resin (B), 10 to 75 parts by mass of aromatic vinyl-based copolymer resin (C) and acid-modified vinyl-based resin (D) in total of 100 parts by mass of polyamide (A), rubber-reinforced vinyl-based graft resin (B), aromatic vinyl-based copolymer resin (C) and acid-modified vinyl-based resin (D), and 0.1 to 40 parts by mass of acid-modified vinyl-based resin (D), The rubber-reinforced vinyl-based graft resin (B) comprises a rubber polymer (b) portion and a resin (m) portion containing a structural unit derived from a vinyl-based monomer grafted to the rubber polymer (b), The weight average particle size of the rubber polymer (b) is 0.20 to 0.70 μm; The thermoplastic resin composition, characterized in that the rubber-reinforced vinyl graft resin (B) contains, as the rubber polymer (b), an ethylene / α-olefin rubber polymer (b1) portion having a melting point of 0 to 100° C. as measured in accordance with JIS K7121-1987.
2. The thermoplastic resin composition according to claim 1, wherein the rubber-reinforced vinyl graft resin (B) is obtained by polymerizing a vinyl monomer including an aromatic vinyl compound in the presence of an ethylene / α-olefin rubber polymer (b1) having a melting point of 0 to 100° C. as measured according to JIS K7121-1987.
3. A molded article made of the thermoplastic resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Gradation control system
JP1995084549A
Thermoplastic resin composition
JP2002212383A
Ecological thermoplastic resin composition
JP2008214585A
Thermoplastic resin composition excellent in low-temperature impact strength
JP2008297334A
Automobile interior trimming part with reduced creak noise
JP2011168186A